Preemption of Bivens Claims: How Clearly Must Congress Speak? - Betsy J. Grey (Washington University Law Quarterly, 1992)
Part I of this Article demonstrates that the Court's approach to congressional remedial schemes has changed significantly since Bivens. Part II of the Article investigates whether this change in approach is warranted by the principle that, when filling gaps in federal legislation (i.e., creating federal common law), the Court should exercise caution because it is acting in an area primarily entrusted to Congress. In Part III, the Article contrasts the Court's approach in the Bivens line of cases to its approach in the federal-state preemption area, where the Court is faced with a similar problem of determining whether one remedial scheme (that of a state) may coexist with another remedial scheme (that of Congress).
Keywords: Exclusive & concurrent legislative powers; Constitutional law -- United States; Remedies (Law)